Final height in girls with Turner's syndrome treated with once or twice daily growth hormone injections. Issue 1 (1st January 1999) - Sas, Th C J; Keizer-Schrama, S M P F de Muinck; Stijnen, Th; van Teunenbroek, A; Hokken-Koelega, A C S; Waelkens, J J J; Massa, G G; Vulsma, Th; Gerver, W J; Reeser, H M; de Waal, H E Delemarre-van; Jansen, M; et al.
Abstract : OBJECTIVES: To study final height in girls with Turner's syndrome treated with once or twice daily injections of growth hormone (GH) in combination with low dose ethinyl oestradiol. DESIGN: Until final height was reached, the effect of fractionated subcutaneous injections given twice daily was compared with once daily injections of a total GH dose of 6 IU/m 2 /day. Twice daily injections were given as one third in the morning and two thirds at bedtime. All girls concurrently received low dose oestradiol (0.05 μg ethinyl oestradiol/kg/day, increased to 0.10 μg/kg/day after 2.25 years). PATIENTS: Nineteen girls with Turner's syndrome aged ⩾ 11 years (mean (SD) 13.6 (1.7) years). MEASUREMENTS: To determine final height gain, we assessed the difference between the attained final height and the final height predictions at the start of treatment. These final height predictions were calculated using the Bayley-Pinneau (BP) prediction method, the modified projected adult height (mPAH), the modified index of potential height (mIPHRUS ), and the Turner's specific prediction method (PTSRUS ). RESULTS: The gain in final height (mean (SD)) was not significantly different between the once daily and the twice daily regimens (7.6 (2.3) v 5.1 (3.2) cm). All girls exceeded their adult height prediction (range, 1.6–12.3 cm). Thirteen of the 19 girls had a final height gain > 5.0 cm. Mean (SD) attained final height was 155.5 (5.4) cm. A "younger bone age" at baseline and a higher increase in height standard deviation score for chronological age (Dutch–Swedish–Danish references) in the first year of GH treatment predicted a higher final height gain after GH treatment. CONCLUSIONS: Division of the total daily GH dose (6 IU/m 2 /day) into two thirds in the evening and one third in the morning is not advantageous over the once daily GH regimen with respect to final height gain. Treatment with a GH dose of 6 IU/m 2 /day in combination with low dose oestrogens can result in a significant increase in adult height in girls with Turner's syndrome, even if they start GH treatment at a relatively late age.